Monte Barro: an Ostrogothic fortified site in the Alps - Martínez Jiménez, J (Department of Archaeology, 2011)
This paper is a reassessment of the original publications of the fortified site of Monte Barro, near Lake Como in Italy, excavated by G.P. Brogiolo and L. Castelletti, which studies its role within the Ostrogothic frontier system. The site is located on a mountain, overlooking the Po plain, but it is close enough to the Alpine passes to control the access into Italy. Built and fortified during the Ostrogothic period, the site was destroyed during the period of the Gothic Wars in the mid sixth century. Because of its location, its views and fortifications, it would be possible to think that it was a fort, especially as it fits perfectly into the Ostrogothic Alpine fortifications, but neither its finds, nor the presence of the main building fully support this statement. Above all, the presence of a bronze hanging crown seems to indicate that some sort of Gothic noble or official lived at the site, which may give Monte Barro not necessarily the category of villa or palace, but certainly an important role within the Gothic administration, probably linked to the Alpine fortifications.